151k views
5 votes
What is 3b - 5b = 2(b + 4)​

User JorgeO
by
4.7k points

2 Answers

4 votes

3b - 5b = 2(b + 4)

mutiply the bracket by 2

(2)(b)= 2b

(2)(4)= 8

3b-5b=2b+8

-2b= 2b+8

move 2b to the other side

sign changes from +2b to -2b

-2b-2b= 2b-2b+8

-2b-2b= 8

-4b= 8

divide both sides by -4

-4b/-4= 8/-4

Answer: b= -2

User Ivanacorovic
by
5.0k points
6 votes

Answer:


\large \boxed{\text{ b = -2}}

Explanation:


\begin{array}{rcll}3b - 5b & = & 2(b + 4) &\\-2b & = & 2(b + 4) & \text{Simplified left-hand side}\\-2b &= & 2b + 8 & \text{Distributed the 2}\\-4b & = & 8 & \text{Subtracted 2b from each side}\\b & = & \large \boxed{\mathbf{-2}} & \text{Divided each side by -4}\\\end{array}

Check:


\begin{array}{rcl}3(-2) - 5(-2) & = & 2(-2 + 4)\\-6 - (-10)& = & 2(2)\\-6 + 10 & = & 4\\4 & = & 4\\\end{array}

OK.

User Brianbruff
by
5.3k points